Conducting the Needs Assessment #11: Causal Analysis Techniques - Amy Harder (EDIS)
This new 3-page publication in the Conducting the Needs Assessment series provides Extension educators and other service providers with an introduction to two techniques that can easily be used when seeking information about relationships between causes and needs: fishboning and cause and consequence analysis. Written by Amy Harder and published by the UF/IFAS Department of Agricultural Education and Communication. https://edis.ifas.ufl.edu/wc352